Topical azithromycin or ofloxacin for endophthalmitis prophylaxis after intravitreal injection - Romero-Aroca P (Dove Medical Press, 2012)
Pedro Romero-Aroca,1 Laura Sararols,2 Lluis Arias,3 Ricardo P Casaroli-Marano,4 Francisca Bassaganyas51Department of Ophthalmology, Hospital Universitari Sant Joan, Universidad Rovira i Virgili, Reus, 2Department of Ophthalmology, Hospital de Granollers, Granollers, 3Department of Ophthalmology, Hospital Universitari de Bellvitge, Barcelona, 4Instituto Clínico de Oftalmologia, Hospital Clínic de Barcelona, Barcelona, 5Department of Ophthalmology, Hospital de la Sant Creu i Sant Pau, Barcelona, SpainBackground: The number of patients who have undergone intravitreal injections has increased enormously in recent years, but a consensus is still lacking on prophylaxis for endophthalmitis. The aim of this prospective, observational study was to evaluate the prophylactic effect of azithromycin eye drops versus ofloxacin eye drops.Methods: The study was conducted in five hospitals in Spain and included all patients undergoing intravitreal injections of triamcinolone, bevacizumab, ranibizumab, or pegaptanib over one year. Patients received azithromycin 15 mg/g eye drops (twice daily on the day prior to injection and for another 2 days) or ofloxacin 3 mg/g eye drops (every 6 hours on the day prior to injection and for another 7 days).Results: In the azithromycin group, there were 4045 injections in 972 eyes of 701 patients. In the ofloxacin group, there were 4151 injections in 944 eyes of 682 patients. There were two cases of endophthalmitis (0.049%) in the azithromycin group and five (0.12%) in the ofloxacin group. The odds ratio of presenting with endophthalmitis in the ofloxacin group compared with the azithromycin group was 2.37 (95% confidence interval [CI] 1.32–3.72, P < 0.001). There were two cases of noninfectious uveitis after triamcinolone injection in the azithromycin group (0.049%) and two (0.048%) in the ofloxacin group; no significant differences were observed (odds ratio 0.902, 95% CI 0.622–1.407, P = 0.407). Conjunctival hyperemia was observed in 12 cases in the azithromycin group and none in the ofloxacin group.Conclusion: The risk of endophthalmitis was significantly greater with ofloxacin than with azithromycin. These findings provide a valuable addition to the ever-increasing pool of information on endophthalmitis prophylaxis after intravitreal injection, although further large-scale studies are required to provide definitive conclusions.Keywords: endophthalmitis prophylaxis, intravitreal injections, azithromycin, ofloxacin, antibiotics